Effects of a multiprofessional program to treat obesity in the aquatic environment in adults with severe obesity (Research, Society and Development, 2021)
Introduction: The continuous increase in severe obesity and the comorbidities associated with this condition have become epidemic and affect the people of all ages and economic groups. In addition, the predictions are that this problem will become even more serious. Therefore, obesity treatment programs are urgently needed, but are rarely accessible to the low-income population. Objective: To analyze the effects of a multiprofessional obesity treatment program (PMTO) in adults with severe obesity (BMI> 40 kg/m2). Method: 13 people (six women and seven men) participated in the study, with a mean age of 41.2 ± 7 years and an average BMI of 48.3 kg/m2. Anthropometric, clinical, laboratory, and physical fitness assessments were performed, following standardized procedures, pre-intervention and after 24 weeks of a PMTO. Results: BMI, percentage of fat (% Fat), absolute body fat, flexibility, handgrip strength, abdominal strength/resistance showed significant improvements (p